SEMIOTIC THEORY OF MALAM BAINAI DELIVERING IN MINANGKABAU WEDDING CEREMONY - Annisa Karmila; Maya Sari (Universitas Negeri Medan, 2021)
The problem of the study in this research is: how is the procedure for the Malam Bainai process at the Minangkabau community wedding ceremony and what is the meaning contained in the implementation of the Malam Bainai at the Minangkabau community wedding ceremony. The research design used is a qualitative descriptive research method by using Pierce’s theory. Then, the informants of this research are people who understand Minangkabau cultures, such as Masters of art and culture who graduated from the University of arts in Padang Panjang, overseas arts, and culture teachers from Padang Panjang, and people who are members of the Minangkabau community in Medan City. The results showed that the Malam Bainai procedure consisted of four series, namely Bamandi, Meniti kain kuniang, Malam Bainai, and Bakameh-kameh. The meaning of the Malam Bainai ceremony is carried out as a form of cultural heritage that has been carried out from generation to generation and as a form of releasing girls from their parents to become brides and companions in other people's lives.Keywords: Linguistics, Semiotics, Malam Bainai, Minangkabau Wedding Ceremony